Membedah Antonomasia: Kritik dan Identitas Sosial dalam Novel Namaku Alam karya Leila S. Chudori - Winnarny Nurul Listary; Wahya Wahya; Wagiati Wagiati (Universitas Nahdlatul Wathan Mataram, 2026)
This research discusses the types, functions, and meanings of antonomasia as social criticism and identity in the novel My Name is Alam by Leila S. Chudori. This research aims to contribute to the advancement of knowledge in the field of language, especially in stylistic studies. This research uses a qualitative-descriptive method with a stylistic approach and antonomasia theory. Descriptive data for qualitative research consists of written words from subjects in the novel Namaku Alam by Leila S. Chudori. In this research, the descriptive data used are only written words used as language symptoms. The results of this research show that antonomasia in the novel Namaku Alam by Leila S. Chudori is used to represent criticism and social identity. Antonomasia in literary works is formed based on the author's writing style. The conclusion of this research is that antonomasia is divided into two types, namely, group and persona, and five main functions, namely as a label or self-identity, nickname, praise or satire, pseudonym (other name), and aesthetics or entertainment.